Expression of USP18 and IL2RA Is Increased in Individuals Receiving Latent Tuberculosis Treatment with Isoniazid. (6th December 2019) - de Oyarzabal, Eleane; García-García, Lourdes; Rangel-Escareño, Claudia; Ferreyra-Reyes, Leticia; Orozco, Lorena; Herrera, María Teresa; Carranza, Claudia; Sada, Eduardo; Juárez, Esmeralda; Ponce-de-León, Alfredo; Sifuentes-Osornio, José; Wilkinson, Robert J.; et al.
Abstract : Background . The treatment of latent tuberculosis infection (LTBI) in individuals at risk of reactivation is essential for tuberculosis control. However, blood biomarkers associated with LTBI treatment have not been identified. Methods . Blood samples from tuberculin skin test (TST) reactive individuals were collected before and after one and six months of isoniazid (INH) therapy. Peripheral mononuclear cells (PBMC) were isolated, and an in-house interferon- γ release assay (IGRA) was performed. Expression of chemokine ligand 4 (CCL4), chemokine ligand 10 (CXCL10), chemokine ligand 11 (CXCL11), interferon alpha (IFNA), radical S-adenosyl methionine domain-containing 2 (RSAD2), ubiquitin-specific peptidase 18 (USP18), interferon-induced protein 44 (IFI44), interferon-induced protein 44 like (IFI44L), interferon-induced protein tetratricopeptide repeats 1(IFIT1), and interleukin 2 receptor subunit alpha (IL2RA) mRNA levels were assessed by qPCR before, during, and after INH treatment. Results . We observed significantly lower relative abundances of USP18, IFI44L, IFNA, and IL2RA transcripts in PBMC from IGRA-positive individuals compared to levels in IGRA-negative individuals before INH therapy. Also, relative abundance of CXCL11 was significantly lower in IGRA-positive than in IGRA-negative individuals before and after one month of INH therapy. However, the relative abundance of CCL4, CXCL10, and CXCL11 mRNA was significantly decreased and that of IL2RA and USP18 significantly increased after INH therapy, regardless of the IGRA result. Our results show that USP18, IFI44L, IFIT1, and IL2RA relative abundances increased significantly, meanwhile the relative abundance of CCL4, CXCL11, and IFNA decreased significantly after six months of INH therapy in TST-positive individuals. Conclusions . Changes in the profiles of USP18, IL2RA, IFNA, CCL4, and CXCL11 expressions during INH treatment in TST-positive individuals, regardless of IGRA status, are potential tools for monitoring latent tuberculosis treatment.